DESAIN RENCANA PEMBELAJARAN BERBASIS PEDAGOGI HIJAU UNTUK MAHASISWA CALON GURU BIOLOGI FKIP UNIVERSITAS RIAU - Astrid Riauda Putriana; Firdaus L.N '; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this research is design of lesson plan based green pedagogy for Biology pre-teacher students FKIP University of Riau. The development was conducted at Biology Education University of Riau. The research held on January until June 2015. Datawere collected byfillingthe validity of the assessment sheet by each validator. Collected datas were analyzed by descriptive statistics. Results of the validity of development lesson plan green pedagogy meet I-XVI are; 3,18; 3,16; 3,19; 3,27; 3,17; 3,28; 3,22; 3,29; 3,17; 3,21; 3,17; 3,28; 3,18; 3,15; 3,16 and 3,20 with valid category. Results of limiting test is 86,25% with very valid. On the last stage of the research, a limiting test on the biology students. Based on the research’s results can be concluded that the design of lesson plan based green pedagogy for Biology pre-teacher students FKIP University of Riau was done with the ADDIE model that consists of some phase, start from analyze, design, develop until limiting test. Based on the results of validation, lesson plan design green pedagogy could be implemented with the field test.Keywords: Lesson plan, learning, green pedagogy